Metroidvania ecologies: Exploration and the environmental imagination in Hollow Knight and Rain World - Andriano, Angelo Maria; Caracciolo, Marco (Eludamos: Journal for Computer Game Culture, 2025)
Metroidvania games are characterized by highly interconnected levels that open up as the player acquires new skills or knowledge of the game world. In this article, we argue that the spatial interconnectedness of the Metroidvania genre strongly resonates with ecological theories foregrounding human–nonhuman enmeshment as well as nonhuman autonomy. Discussing two recent Metroidvania titles, Hollow Knight (Team Cherry, 2017) and Rain World (Videocult, 2017), we show how these games consistently challenge the player’s environmental imagination, and particularly notions of human mastery over the nonhuman world. They do so on multiple levels: by evoking rich postapocalyptic settings that resist the player’s attempts to project anthropocentric assumptions onto the games; by confronting players with nonhuman characters and lore that remain unreadable and opaque; and by creating dynamically evolving game worlds in which nonhuman behavior feels unruly and unpredictable. Most importantly, though, the two games suggest ecosystemic interconnectedness by defamiliarizing the players’ understanding of exploration as the linear traversal of spaces that can be fully controlled and depleted. Through this discussion, we aim to situate Metroidvania games within the growing archive of ecogaming, explaining what is so unique about the genre’s approach to the environmental imagination.